The Handbook of Security
XXXIII, 1049 p.
Keywords: The substantially revised second edition of the Handbook of Security provides the most comprehensive analysis of scholarly security debates and issues to date. Including contributions from some of the world's leading scholars it critiques the way security is provided and managed.